2007
DOI: 10.1177/000348940711600416
|View full text |Cite
|
Sign up to set email alerts
|

Laryngoscopies in the Obese: Predicting Problems and Optimizing Visualization

Abstract: An appropriate clinical examination may help predict a difficult airway. However, further studies are warranted to fully characterize the anatomic predictors of a difficult laryngeal exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
(13 reference statements)
1
13
0
1
Order By: Relevance
“…Furthermore, undue force during ETT insertion is not necessary because this is likely to result in injury. These provisions have been reiterated numerous times in almost every case report issued thus far; therefore, they should be reflected when using videolaryngoscopy for intubation …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, undue force during ETT insertion is not necessary because this is likely to result in injury. These provisions have been reiterated numerous times in almost every case report issued thus far; therefore, they should be reflected when using videolaryngoscopy for intubation …”
Section: Discussionmentioning
confidence: 99%
“…20 Obesity as a predictor of the difficult airway has been well studied, and specific challenges are known to be inherent to intubation of obese patients. [21][22][23] Obese patients may have crowding and distortion of the oropharynx, limited neck extension, a higher incidence of comorbid conditions, and a lower tolerance for apnea and tissue hypoxia. 21,23,24 Holmberg et al 21 observed that class I/II obesity (body mass index Ͼ 30 kg/m 2 and Ͻ 40 kg/m 2 ) in patients was not associated with difficult intubation, whereas patients with body mass index Ͼ 40 kg/m 2 had higher rates of difficult intubation.…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, the ability of airway parameters to predict laryngoscopy view and difficult intubation in the obese patient is questionable [10][11][12]. To evaluate and compare intubation difficulty in obese and non-obese patients, we performed a prospective, controlled study using IDS scores, intubation duration measurements, and lowest SaO 2 levels.…”
Section: Introductionmentioning
confidence: 99%